SOSIALISASI TRADISI PURNAMA DI KARANGREJO, DESA WISATA BOROBUDUR MAGELANG - Setyani, Turita Indah; Tjahjandari, Lily (UI Scholars Hub, 2025)
The development of digital technology, while offering many conveniences, has also led the younger generation to become overly absorbed in their gadgets. Many young people today find it difficult to detach themselves from their devices. This situation can have negative effects on children's psychological development, as they need both motor and social stimulation. Traditional children's games offer significant benefits for physical and mental growth. Coinciding with the Summer Solstice event in Borobudur—when the Moon is positioned directly above Borobudur's coordinates—the Summer Solstice Festival was held in Karangrejo Tourism Village, Magelang. In support of this festival, a community service program was conducted to promote the “Full Moon Tradition. In Javanese society, the full moon tradition in the past was a time when communities would gather under the full moon and engage in various activities, such as playing traditional games, dancing, singing, and performing full moon meditation. This community service program involved students and residents of Karangrejo Tourism Village in presenting a variety of artistic activities during the full moon night. The goal of this initiative is to promote literacy about the full moon tradition, which has become increasingly rare in the era of digital technology.